Konstruksi Kegiatan Market Day dalam Menumbuhkan Jiwa Enterpreneurship Siswa - Sari, Jusniati; Santosa, Sedya; Nurdin, Muh Nur Islam (Lembaga Sosial Rumah Indonesia, 2024)
Purpose - This research examines the construction of Market Day activities to foster students' entrepreneurial spirit. Market day activities are held at SD Negeri Demangan Yogyakarta at the end of every semester.Methods - This research uses a qualitative approach, a case study type of research, with the market day coordinator as the subject, namely the principal and teachers. Data collection was carried out through observation, interviews, and documentation studies. The data analysis techniques used are data reduction, data presentation, and conclusion.Findings - The results of the research show that market day activities can foster students' entrepreneurial spirit, train leadership and responsibility for goods sold, and teach about counting, which can improve students' thinking patterns. The school's efforts to foster students' entrepreneurial spirit through market day activities at SD Negeri Demangan Yogyakarta include: 1) guiding students to always be involved in market days, 2) instilling an attitude of independence; 3) growing self-confidence; and 4) getting used to the culture of queuing.Research Implications - This article recommends that Market Day activities can be an alternative for schools to foster students' entrepreneurial spirit.